Leaf Lettuce Cultivation Technology, Zoned and Widespread Varieties - Boymirov Abdumalik Xo’shboqovich; Qulmonova Tursunoy; Gumatova Marjona (International Journal on Integrated Education, 2022)
Lettuce grows well in soils rich in various nutrients. Lettuce prefers soils with organic and mineral fertilizers. If the soil is well fertilized, lettuce can be planted after potatoes, cucumbers, peas, and tomatoes. If you plant radishes and radishes, then the salad will not work. For growing lettuce seedlings, a substrate is prepared, consisting of one part of humus or compost, two parts of humus-rich soil and one part of sand. For growing leafy vegetables, 400-500 grams per hectare of class I seeds with a purity of 98% and a yield of at least 85%.